Wykonaj działania :

-5t-(-4t)-7t =
-k-k-(-k)+(-8k) =
-(-3m)-2m+(-4m) =

Zredukuj wyrazy podobne i zapisz w prostszej postaci :

a) 2x+y-x+4y
b) 3x-2+14x
c) 8x-4-15x-7
d) -5x+3y-6x-13y
e) 0,5x+2,1y +3,7x-0,2y
f) ¹/₃x-y-y-⅔x

Z góry dziękuje.
Daje naj.

2

Odpowiedzi

2010-03-01T17:36:27+01:00

-5t-(-4t)-7t = -5t +4t -7t= -8t
-k-k-(-k)+(-8k) = -2k +k -8k = -9k
-(-3m)-2m+(-4m) =3m -2m -4m = -3m

Zredukuj wyrazy podobne i zapisz w prostszej postaci :

a) 2x+y-x+4y=x +5y
b) 3x-2+14x= 17x -2
c) 8x-4-15x-7= -7x -11
d) -5x+3y-6x-13y= -11x -10y
e) 0,5x+2,1y +3,7x-0,2y= 4,2x 1,9x
f) ¹/₃x-y-y-⅔x= -1/3x -2y
1 1 1
Najlepsza Odpowiedź!
2010-03-01T17:42:15+01:00
-5t-(-4t)-7t = -5t+4t-7t= -1t-7t= -8t

-k-k-(-k)+(-8k) =-2k+k-8k = -1k-8k=-9k

-(-3m)-2m+(-4m) =3m-2m-4m = 1m-4m = -3m

a) 2x+y-x+4y = 2x-x+y+4y = x+5y

b) 3x-2+14x = 3x+14x-2 = 17x-2

c) 8x-4-15x-7 = 8x-15x-4-7 = -7x-11

d) -5x+3y-6x-13y = -5x-6x+3y-13y = -11x-10y

e) 0,5x+2,1y +3,7x-0,2y = 0,5x+3,7x+2,1y-0,2y = 4,2x+1,9y

f) ¹/₃x-y-y-⅔x = ¹/₃x-⅔x-y-y = -¹/₃x-2y